ADSORPTION OF AFLATOXIN B1 IN CORN ON NATURAL ZEOLITE AND BENTONITE - Nuryono Nuryono; Ali Agus; Sri Wedhastri; Y.M.S. Maryudhani; Deni Pranowo; Yunianto Yunianto; Ebrahim Razzazi-Fazeli (Universitas Gadjah Mada, 2012)
A study on adsorption of AFB1 in corn (kernel and grained) on natural zeolite and bentonite has been investigated. The first work was adsorption in a batch system of standard AFB1 solution on adsorbents. Some factors such as contact time, concentration of AFB1 and particle size of adsorbent were evaluated. The amount of AFB1 adsorbed was calculated based on the difference of AFB1 concentration before and after adsorption determined by high performance liquid chromatography (HPLC) method. Adsorption of AFB1 in corn sample was emphasized by mixing aqueous suspension of sample with adsorbent. Concentration of AFB1 in suspension was analyzed by enzyme-linked immuno-sorbent assay (ELISA) method. Result shows that adsorption of AFB1 on adsorbents of natural zeolite and bentonite is very fast. Within 15 min 99% of AFB1 (200 ng/mL) has been adsorbed by 25 mg of bentonite and 96% by zeolite. The particle size higher than 200 mesh did not give significant effect on the AFB1 adsorption capability. Effectiveness of zeolite in adsorbing AFB1 is lower than that of bentonite. Capability in reducing AFB1 contamination in corn samples (kernel and meal) for both adsorbents is lower than that in standard solution.